Increasing Competitive Advantage Through Creativity and Innovative Behavior: The Moderating Role of Digital Leadership - Tonny Yuwanda; Leni Gustina; Shinta Bella (Universitas Mercu Buana, 2023)
Objectives: This study aims to investigate the importance of strategy to increase competitive advantage which was studied from creativity, Innovative Work Behavior, and preceded by psychological empowerment through the mediating effects of the creativity, creative behavior, and moderation of digital leadershipMethodology: This study uses a quantitative approach where questionnaires are distributed to 254 SMEs in West Sumatra, Indonesia. The analysis technique used is path analysis using SEM-PLS.Finding: The results showed that psychological empowerment has a direct effect on creativity and innovative work behavior but has no effect on competitive advantage. Creativity affects innovative work behavior but does not affect competitive advantage. Innovative work behavior affects competitive advantage. Creativity mediates psychological empowerment for innovative work behavior but does not mediate competitive advantage, and innovative work behavior mediates psychological empowerment and creativity for competitive advantage. Digital leadership mediates creativity into innovative work behaviors and innovative work behaviors into competitive advantages but does not mediate psychological empowerment and creativity into competitive advantages.Conclusion: To compete in the current era, creativity is needed based on the wishes of the employees themselves so that it will be easy to shape the innovative behavior of employees. This innovative behavior will be the initiator of the development of SMEs. In addition, leaders should follow trends and technological developments and guide employees to improve their IT insight. Thus, it will accelerate the behavior change to be innovative and be able to win the competition in the current technological era.